Disfemisme dan Eufemisme pada Terjemahan Indonesia-Inggris dalam Film "Agak Laen” - Ghina Qolbi; Agsel Fia Steviw Ade Ratna; Kiki Ratnasari (PRASASTI: Journal of Linguistics, 2026)
Translation in movies is very influential in terms of language use on how the message is conveyed to the audience. This study aims to describe and analyze the changes of dysphemism expressions in the Indonesian dialogues of “Agak Laen” film characters (BSa) translated into English (BSu). This research belongs to qualitative research. The data used is in the form of utterances in the translated dialog of the film “Agak Laen” which contains dysphemism expressions. Data collection in this study used the listening method with note-taking technique. The data analysis uses the theory of skopos which makes the purpose of the target language as a determinant of changes in the expression of dysphemism. The results show the dominance of dysphemism expressions that remain dysphemisms when translated into BSa. In addition, there are also dysphemisms that change into euphemisms when translated into BSa to suit the purpose of BSa.